Transcriptome Analysis of Stem and Globally Comparison with Other Tissues in Brassica napus - Miao, Liyun; Zhang, Libin; Raboanatahiry, Nadia; Lu, Guangyuan; Zhang, Xuekun; Xiang, Jun; Gan, Jianping; Fu, Chunhua; Li, Maoteng (Frontiers in Plant Science, 2016)
Brassica napus is one of the most important oilseed crops in the world. However, there is currently no enough stem transcriptome information and comparative transcriptome analysis of different tissues, which impedes further functional genomics research on B. napus. In this study, the stem transcriptome of B. napus was characterized by RNA-seq technology. Approximately 13.4 Gb high-quality clean reads with an average length of 100 bp were generated and used for comparative transcriptome analysis with the existing transcriptome sequencing data of roots, leaves, flower buds and immature embryos of B. napus. All the transcripts were annotated against GO and KEGG databases. The common genes in five tissues, differentially expressed genes (DEGs) of the common genes between stems and other tissues, and tissue-specific genes were detected, and the main biochemical activities and pathways implying the common genes, DEGs and tissue-specific genes were investigated. Accordingly, the common transcription factors (TFs) in the five tissues and tissue-specific TFs were identified, and a TFs-based regulation network between TFs and the target genes involved in “Phenylpropanoid biosynthesis” pathway were constructed to show several important TFs and key nodes in the regulation process. Collectively, this study not only provided an available stem transcriptome resource in B. napus, but also revealed a valuable comparative transcriptome information of five tissues of B. napus for future investigation on specific processes, functions and pathways.